Innovative Pedagogical Approaches in Organization of Technological Educational Processes - Dusyarov Khudoymurod Chorshanbiyevich (Peerian Journals Publishing, 2022)
This article conveys the purpose, content and essence of the use of innovations, information technology and advanced innovative pedagogical technologies in the organization of the process of technological education in the Republic.
Keywords: Pedagogy; education system; technological education; innovation